Artificial intelligence, digital social networks, and climate emotions - Victor Galaz; Hannah Metzler; Caroline Schill; Therese Lindahl; Stefan Daume; Arvid Marklund; Antonio J. Castro; Jennifer Bard; Timon McPhearson; Diego Galafassi; Helge Peters (npj Climate Action)
Abstract Emotions relate to climate change action in various ways. Here we elaborate on how the expansion of digital social networks and advances in artificial intelligence, ranging from recommender systems to generative AI, may affect the way people perceive and engage emotionally on climate change. We develop a simple framework that links individual and collective emotions, AI, and climate action, and suggest three critical areas in need of further investigation.